Databases: Working tools for networks - Meschy F.; Morand-Fehr P.; Bas P.; Sauvant D. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
The objectives of the paper are to inform the network's members of our laboratory's experience on the creation of databases and their utilization in meta-analysis in order to analyze bibliographic or experimental data in the field of sheep and goat nutrition. It would be possible to create new databases or to open the existing databases to interested colleagues. But to be successful, it would be necessary to proceed with a strict strategy. First, to clarify the objectives and organization of the database if it is already working, the kind and quality of data to be included and the conditions to be appointed for database members who can enrich and use the databank. The rules of management must be well defined. The paper gives examples of the actual difficulties resulting from a meta-analysis using a database on the factors modifying the composition of adipose deposits in lambs. The meta-analysis from databases is a good strategy to create new information and general rules but the risks of an inadequate interpretation exist if the scientific approach used is not very rigorous.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)